EFFECT OF LEARNING MODEL APPLICATION OF GUIDED LABORATORY INQUIRY TO LOGICAL THINKING ABILITY OF STUDENTS ON HEAT TO ELECTRICITY CONVERSION MATERIAL - Fauziah, Fitri; Suyanto, Eko; Wahyudi, Ismu; Herlina, Kartini (Jurnal Pendidikan Matematika dan IPA, 2022)
This reseach aims to determine the application effect of guided inquiry laboratory model on students"™ logical thinking ability on the material of heat to electricity conversion. The population in this reseach were all students of class XII MIA at SMA Negeri 15 Bandarlampung for the 2019/2020 academic year. The technique used is purposive sampling, so that the sample in class XII MIA 1 is obtained in the form of a one group pretest-posttest design. The process of collecting data using interview techniques as a preliminary study and through pretest-posttest. The test question used is the Logical Thinking Test which measures five indicator"™s of logical thinking. Hypothesis testing is done by using Paired Sample T-Test. The results of the analysis showed that the average difference between the posttest and pretest scores was 30.80 for all indicators. Data analysis also obtained an average n-gain of 0.55 which is included in the medium category. The n-gain test was also carried out on each indicator and was in the medium category. The variable controlling indicator shows n-gain of 0.65; probabilistic reasoning of 0.66; correlational reasoning of 0.62; proportional reasoning of 0.51; and combinatorial 0,36. Based on the entire analysis test, the results of the reseach showed that there was a significant effect of applying the guided inquiry laboratory model on the students"™ logical thinking ability on the material of heat to electricity conversion.